Fatal outcome in coinfection between SARS-CoV-2 and dengue - Ramírez, Juan (2023)
COVID-19, a result of SARS-CoV-2 infection, is characterized by a primary impact on the alveolar cells of the respiratory system. However, the possibility of co-infection with dengue virus (DENV) has been documented, triggering a severe systemic inflammatory response. This heightened inflammatory response leads to a substantial release of viral RNA into the cellular cytoplasm, which amplifies the viral load and aggravates lung damage, causing multiple organ dysfunction. In the case of DENV, the infection induces a cytokine storm that increases capillary permeability, resulting in plasma leakage. The present report aims to describe a case of an adult male patient with COVID-19 and dengue co-infection who had a fatal outcome.